FABRICATION AND MECHANICAL PROPERTIES OF CNT16063 Al COMPOSITES PREPARED BY VACUUM ASSISTED INFILTRATION TECHNIQUE USING CNT-Al PREFORMS - Kucukyildirim, Bedri Onur; Akdogan Eker, Aysegul (ADCOTEC LTD, 2012)
Industrial type multi-walled carbon nanotube (MWCNT) reinforced aluminum (Al) matrix composites are successfully fabricated by vacuum assisted infiltration of Al into the CNTs-Al preform and compressive mechanical properties of these composites are investigated. The compressive properties and hardness of CNT reinforced composites are fairly increased compared with the previous CNT/Al composite studies. Furthermore, our study confirms that the mechanical enhancements of the composites are interrelated with bridging and pulling-out of CNTs in the fracture surfaces. Moreover, the presence of CNTs leads to dispersion strengthening of the matrix because of their nano size.
Keywords: Carbon nanotubes; metal matrix composites; preform; fabrication; casting; Materials Science